Impact of Entrepreneurial Competencies and Coopetition Strategy on Sustainable Performance: A Moderated Mediation Model - It Nguyen Van (Asian Academy of Management Journal, 2025)
This study aims to investigate the effects of entrepreneurial competencies and coopetition strategy on sustainable performance, the mediating role of innovation, and the regulatory role of digitalisation capability. Data were collected from 357 leaders at all levels of business in Ho Chi Minh City, Vietnam. The results showed that both entrepreneurial competencies and coopetition strategy had a significant impact on sustainable performance. Additionally, the innovation factor directly affects sustainable performance and positively mediates the relationship between entrepreneurial competencies and sustainable performance. This is the first study to explore the regulatory role of digitalisation capability in the relationship between coopetition strategy and sustainable performance, as well as how digitalisation capability directly affects sustainable performance positively. This research provides intriguing empirical evidence about an under- researched emerging economy in Asia, namely, Vietnam. Furthermore, the results add to the knowledge in the field of business behaviour research and the alignment of linkages between organisational elements to achieve sustainable performance and suggest meaningful management implications and practical meaning for companies in the context of Ho Chi Minh City, Vietnam, in particular, and similar Asian economies, in general.